Telemedicine in follow-up of pediatric status epilepticus: A resounding success story or just a farce? - Shubham Agrawal; Rachna Sehgal; Rani Gera (Elsevier, 2023)
Objectives: Status epilepticus is a life-threatening medical emergency that presents with a continuous seizure lasting for more than five minutes. Telemedicine can potentially play a role in follow-up care of such patients after discharge from the hospital at reduced patient costs. Whether it is efficacious and leads to patient satisfaction is controversial. Therefore, the primary objective of the present study was to compare video consultation with face-to-face consultation in children aged 1-12 years with tonic-clonic status epilepticus after seven days of discharge for any one of the following critical events-any breakthrough seizure, drug compliance, features of raised intracranial pressure and any adverse events. The secondary objective of the study was to compare cost and patient satisfaction of the two modalities. Methods: Children aged 1-12 years attending Paediatric Emergency of a tertiary care hospital of Northern India with a diagnosis of status epilepticus were enrolled after written informed consent from the parents before completion of their hospital stay. The parents were contacted by the Paediatric Resident on their mobile phone through video calling one day before the scheduled hospital visit. Subsequently, the child was seen directly in hospital on the next day by faculty member/Resident. The information of both interactions was noted on a structured questionnaire. The diagnostic accuracy of telemedicine video consultation for identifying the Critical Clinical Events was estimated using Face-to-Face consultation as the gold standard. Results: Out of the 108 enrolled patients, two patients were lost to follow up. The diagnostic performance of video consultation in identification of any of the Critical Events compared to Face-to-Face Consultation was as follows: Sensitivity: 42%, Specificity: 100%, PPV: 100%, NPV: 89% with overall Diagnostic Accuracy: 90%. The main discrepancy was seen in identification of the drug compliance. The reason for decreased sensitivity was the presence of different caregivers for video and face to face consultation. The average cost of coming to hospital was 362.73 INR whereas no additional cost was required for video consultation. Also, the average time of visiting the hospital was 4 hour and 26 min, whereas the average time of video consultation was 10 min. 100.0% of the participants agreed that the method of Video Consultation was cost effective and time Saving. Majority (92.5%) of the participants were Satisfied with Video Consultation and 82.1% of the participants were willing for the method of video consultation for further follow up of their children. Significance: Diagnostic accuracy of video consultation compared to face to face consultation in children aged 1-12 years with tonic clonic status epilepticus after seven days of discharge is 90%. The cost effectiveness time and patient satisfaction seen with telemedicine are encouraging. Ensuring that the primary caregiver is present for both video and face to face consultation by a prior consent can improve the sensitivity and diagnostic accuracy of video consultation. Categories: : Medical Education, Neurology, Pediatrics